2017
DOI: 10.1093/infdis/jix599
|View full text |Cite
|
Sign up to set email alerts
|

Timing of First Respiratory Virus Detections in Infants: A Community-Based Birth Cohort Study

Abstract: Infants do not always experience respiratory symptoms with their fVDE. Predominance of early HRV detections highlights the need for timing any intervention early in life. fVDEs from other respiratory viruses most commonly occur when maternal vaccines may no longer provide protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 48 publications
9
44
0
Order By: Relevance
“…We found nearly five times more co-detections in our study than were reported from among the first viral detections of those enrolled in a community birth cohort from Brisbane. 3,27 EVs were observed to have an especially low proportion of co-detections in our 2001 sample. As reported in our earlier studies of populations from different years and Australian locations, we again observed that detection of an IFAV, EV, RV or RSV occurred with reduced likelihood of co-detection of any other virus in that patient's sample.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…We found nearly five times more co-detections in our study than were reported from among the first viral detections of those enrolled in a community birth cohort from Brisbane. 3,27 EVs were observed to have an especially low proportion of co-detections in our 2001 sample. As reported in our earlier studies of populations from different years and Australian locations, we again observed that detection of an IFAV, EV, RV or RSV occurred with reduced likelihood of co-detection of any other virus in that patient's sample.…”
Section: Discussionmentioning
confidence: 60%
“…Infants from one to 12 months of age were most likely to be affected by RV or RSV in our convenience sample population; this agreed with findings from the Brisbane community cohort. 3 RV-positive children were second youngest after RSV-positive children while IFAV-positive children were generally older than those positive for any other virus. Interestingly, it is often children younger than 2 years who are affected by severe influenza.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For those of us interested in respiratory viruses, there is a lot to like about the study by Sarna et al that appears in this issue of The Journal of Infectious Diseases [1]. The study analyzes data from a birth cohort established as part of the Observational Research in Childhood Infectious Diseases (ORChID) Project, based in Brisbane, Australia [2].…”
mentioning
confidence: 99%